Configurações e atualizações de gêneros em diferentes suportes : uma análise da resenha e da videorresenha de filmes - Fortes, Ariane Peronio Maria (2016)
This study presents a proposal of genre analysis which occur in two modalities of language and on two genre supports: written and spoken modality and print and digital format, as a video. The genre here analysed is a critical review of movies found in the weekly magazine Veja and the reviews produced on video and posted on Veja s homepage, which are named as video reviews. The general objective was to understand the updating and configuration of the discursive genre movie review in its print and digital form. This study is justified by the need to understand the inherent settings and transformations in discoursive genre which are updated each time new technologies and new modes of communication arise. This work could also contribute to research in the area of genre, its supports and its modalities as well as to study the language in multimídia, being also a contribution to mother tongue teaching and foreign language teaching through genres. The specific objectives were first to identify the compositional construction, theme and style of the printed and video versions of the movie reviews by comparing how these three elements of the genre are configured in each genre. Then, it was analyzed the configuration of print and digital format in which reviews are updated in order to understand the implications in the formal setting in terms of style, theme and compositional construction as well as the interaction of readers with the genre. Finally, we attempted to verify the retextualization processes that occur when transposing the genre from written to spoken modality by analyzing the linguistic resources that used. This study was anchored in Bakhtinian assumptions in relation to language and genres as well as their contemporary followers as Marcuschi, Fiorin, Sobral, Rojo among others. The study and analysis of the genre support was performed used has its base on Távora s thesis and the verification of retextualization processes followed Marcuschi studies. The research showed that the genre movie review maintains its function but updates a new form of interaction and language because of the possibilities of digital media and the multimodalities that are possible because of it